2024
DOI: 10.1002/pro.4901
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of broadly‐neutralizing antibodies against brown recluse spider and Gadim scorpion sphingomyelinases using consensus toxins as antigens

Esperanza Rivera‐de‐Torre,
Stefanos Lampadariou,
Mark Møiniche
et al.

Abstract: Broadly‐neutralizing monoclonal antibodies are becoming increasingly important tools for treating infectious diseases and animal envenomings. However, designing and developing broadly‐neutralizing antibodies can be cumbersome using traditional low‐throughput iterative protein engineering methods. Here, we present a new high‐throughput approach for the standardized discovery of broadly‐neutralizing monoclonal antibodies relying on phage display technology and consensus antigens representing average sequences of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This methodology enables the discovery of specific antibodies against the most medically relevant toxins, regardless of their abundance within the venoms or immunogenicity 20 . Phage display technology can furthermore facilitate the discovery of cross-neutralizing antibodies (antibodies that can neutralize more than one toxin isoform) through cross-panning strategies 17 , 19 , 21 or selections against recombinantly produced consensus antigens (i.e., antigens designed to represent the ‘average’ of several different proteins) 22 . Finally, it has been shown that monoclonal antibodies can be combined as carefully generated oligoclonal mixtures, allowing for the neutralization of multiple toxins by a single cocktail 18 .…”
Section: Introductionmentioning
confidence: 99%
“…This methodology enables the discovery of specific antibodies against the most medically relevant toxins, regardless of their abundance within the venoms or immunogenicity 20 . Phage display technology can furthermore facilitate the discovery of cross-neutralizing antibodies (antibodies that can neutralize more than one toxin isoform) through cross-panning strategies 17 , 19 , 21 or selections against recombinantly produced consensus antigens (i.e., antigens designed to represent the ‘average’ of several different proteins) 22 . Finally, it has been shown that monoclonal antibodies can be combined as carefully generated oligoclonal mixtures, allowing for the neutralization of multiple toxins by a single cocktail 18 .…”
Section: Introductionmentioning
confidence: 99%